2011
DOI: 10.1055/s-0031-1291447
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic vs. laparoscopic gastrojejunostomy for duodenal obstruction: a randomized study in a porcine model

Abstract: Purely endoscopic gastrojejunostomy using the developed technique and devices is feasible and can result in adequate relief of duodenal obstruction. Endoscopic anastomoses tend to be smaller than laparoscopic anastomoses, with the procedures being more time-consuming and associated with higher complication rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 9 publications
0
9
0
1
Order By: Relevance
“…In 2005 were performed the first NOTES procedures, currently performed on humans, techniques based on a transluminal access for transgastric access. The first endoscopic experimental approach for pure NOTES gastrojejunal anastomosis was recently developed and tested in porcine non-survival and survival experiments 22 . In that regard, we have recently explored the concept of creating an experimental “pure” NOTES gastrojejunal anastomosis in different pig models to achieve a NOTES transgastric bypass 23 24 .…”
Section: Discussionmentioning
confidence: 99%
“…In 2005 were performed the first NOTES procedures, currently performed on humans, techniques based on a transluminal access for transgastric access. The first endoscopic experimental approach for pure NOTES gastrojejunal anastomosis was recently developed and tested in porcine non-survival and survival experiments 22 . In that regard, we have recently explored the concept of creating an experimental “pure” NOTES gastrojejunal anastomosis in different pig models to achieve a NOTES transgastric bypass 23 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic experimental approaches for GJA using NOTES were recently developed and tested in porcine nonsurvival and survival experiments [6 -8]. Although it has been shown to be feasible, our group and others confirmed that NOTES GJA in an experimental porcine model can be technically difficult using the currently available endoscopic techniques and devices [9,10]. Moreover, the lack of a specific sutur-Background and study aims: Various techniques using surgical and natural orifice transluminal endoscopic surgery (NOTES) have been evaluated to create a gastrojejunal bypass.…”
mentioning
confidence: 60%
“…Plusieurs tentatives de gastroentéro-anastomoses ont été réalisées avec des approches hybrides ou endoscopiques pures, utilisant notamment de nombreuses méthodes pour la réalisation de la suture, telles que l'usage de T-tags [1][2][3] ou encore d'autres prototypes de suture [4,5]. Une d'elles notamment, était une étude prospective, comparative et randomisée, d'AGJ avec approche laparoscopique, mais l'absence de système de suture spécifique résulte en une procédure très longue et avec un taux de lâchage anastomotique important [1,3].…”
Section: By Pass Endoscopique Par Notes Marc Barthet Geoffroy Vanbieunclassified